PANORAMA OF RECYCLING AND SELECTIVE COLLECTION IN BRAZIL: ANALYSIS OF STATE RESULTS AND RESPECTIVE CAPITALS - de Araújo Dantas, Maria Wagna; Alves da Silva , Wagner Luiz; de Lima Costa , João Paulo; Gomes Ferreira, José (Revista Aval, 2025)
As a result of the degradation of the planet and the incessant demand for materials extracted from nature, the issue of solid waste recycling has been occupying a prominent place on the public agenda, intersecting with circular economy and ecosystem recovery policies. The article analyzes, on the one hand, the debate on the issue of selective collection and recycling as a socio-environmental problem that, as such, requires society's engagement in the implementation of public policy, as the issue concerns everyone and permeates their daily lives. On the other hand, it also analyzes the issue in Brazil based on the National Solid Waste Policy, addressing recycling, selective collection and the role of recyclable material collectors. In order to achieve this objective, literature review, document analysis, and data collection and analysis on the sector were carried out.